2018
DOI: 10.24252/jb.v6i1.5153
|View full text |Cite
|
Sign up to set email alerts
|

Kesulitan Guru Dalam Pengembangan Keterampilan Berpikir Tingkat Tinggi Siswa Dalam Pembelajaran Biologi Kelas Xii Di Sma Negeri 2 Gowa

Abstract: This study aims to determine students' higher order thinking skills, know the difficulties faced by the teachers and find out the solution adopted in overcoming the difficulties of teachers in developing higher level thinking skills in class XII student at SMAN 2 Gowa. This type of research is descriptive qualitative research. Purposive sample in this study is three biology teachers and 67 students of class XII in school SMAN 2 Gowa. The research instruments used in data collection is divided into two, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
6
0
6
Order By: Relevance
“…HOTS meliputi keterampilan berpikir yang membutuhkan lebih dari sekadar mengingat atau menghafal informasi [11]. Peran guru sebagai fasilitator dalam pembelajran diharapkan dapat meningkatkan kemampuan peserta didik serta mendorong untuk berpikir secara luas dan mendalam [12]. Guru memiliki peran penting dalam memberikan inovasi pada pelaksanaan kegiatan pembelajaran dengan cara ketepatan pemilihan model pembelajaran, dikarenakan berpengaruh terhadap hasil belajar peserta didik yang menjadi faktor penting dalam proses pembelajran yakni sebagai tolak ukur keberhasilan pendidikan [13].…”
Section: Hotsunclassified
“…HOTS meliputi keterampilan berpikir yang membutuhkan lebih dari sekadar mengingat atau menghafal informasi [11]. Peran guru sebagai fasilitator dalam pembelajran diharapkan dapat meningkatkan kemampuan peserta didik serta mendorong untuk berpikir secara luas dan mendalam [12]. Guru memiliki peran penting dalam memberikan inovasi pada pelaksanaan kegiatan pembelajaran dengan cara ketepatan pemilihan model pembelajaran, dikarenakan berpengaruh terhadap hasil belajar peserta didik yang menjadi faktor penting dalam proses pembelajran yakni sebagai tolak ukur keberhasilan pendidikan [13].…”
Section: Hotsunclassified
“…Factors that cause problems in the world of education are not only caused by teachers but facilities and students because the three components are very closely related to support progress in the world of education. Overcoming problems in class every teacher is different so that various strategies developed by others cannot be used by all teachers [10]. The teacher has the responsibility to make the maximum effort, so that the class can be managed well.…”
Section: Introductionmentioning
confidence: 99%
“…In general, teachers agree that HOTS learning is important to be taught to students at all levels (Kim et al, 2019;Schulz & FitzPatrick, 2016;Tyas et al, 2019). However, several studies have shown that teachers have difficulty in compiling HOTS questions (Driana & Ernawati, 2019;Ichsan et al, 2019;Jensen et al, 2014;Nurhayani et al, 2018). 21st century skills include critical thinking competencies, problem solving, creative thinking, meta-cognition, communication, digital and literacy technology (Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%